2013
DOI: 10.12665/j122.hahn
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Manufacture and Release of a GMP Batch of Avian Influenza A(H7N9) Virus-Like Particle Vaccine Made Using Recombinant Baculovirus-Sf9 Insect Cell Culture Technology

Abstract: ovavax reported that, in 28 days following public release of the avian influenza A/Anhui/1/2013 (H7N9) virus gene sequences, its recombinant DNA and baculovirus-Spodoptera frugiperda cell culture-based technology was used to produce a virus-like particle vaccine to avian influenza A(H7N9) virus, and murine animal challenge studies were initiated. [1] This report describes Novavax's manufacturing process and the coordinated timing of critical activities necessary to produce and release a clinical batch of avian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 13 publications
0
29
0
Order By: Relevance
“…Although higher impurity removal steps are described for chromatography processes, the recovery yields are usually lower and/or the purification design is strain‐dependent . Complex purification processes were developed for clinical purposes combining membrane filtration, centrifugation, and ultracentrifugation as well as chromatography, highly impacting the product recovery, process time, and cost.…”
Section: Introductionmentioning
confidence: 99%
“…Although higher impurity removal steps are described for chromatography processes, the recovery yields are usually lower and/or the purification design is strain‐dependent . Complex purification processes were developed for clinical purposes combining membrane filtration, centrifugation, and ultracentrifugation as well as chromatography, highly impacting the product recovery, process time, and cost.…”
Section: Introductionmentioning
confidence: 99%
“…Werner et al (2010) ascribe this fact to the more homogeneous energy dissipation and reduced foaming detected in these bioreactor types in comparison to stirred systems [19]. Nevertheless, single-use stirred bioreactors used, for example, by Novavax for its Sf-9/BEVS-based VLP vaccine productions are also suitable and even scalable up to 2 m 3 [18,20]. Nevertheless, single-use stirred bioreactors used, for example, by Novavax for its Sf-9/BEVS-based VLP vaccine productions are also suitable and even scalable up to 2 m 3 [18,20].…”
Section: Introductionmentioning
confidence: 99%
“…Yet another emerging method is ultrafiltration. 8 L; Hahn et al, 2013), continuous chromatography (e.g. UF1 represents a published protocol employing a series of dead-end and tangential-flow filters (Heinemann et al, 2014).…”
Section: Selection Of Ev Harvest Technologiesmentioning
confidence: 99%
“…In general, largerscale versions of each method may be possible with continuous-flow ultracentrifuges (e.g. 8 L; Hahn et al, 2013), continuous chromatography (e.g. 16 L; Bisschops, Frick, & Levison, 2016), and other industrial equipment, but feasibility of their use for EVs has not been reported.…”
Section: Selection Of Ev Harvest Technologiesmentioning
confidence: 99%